1997
DOI: 10.1111/j.1471-6712.1997.tb00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Male Nurses—Reasons for Entering and Experiences of Being in the Profession

Abstract: In order to illuminate male nurse teachers' and nurse students' reasons for choosing to become nurses, and their experiences and positions within the profession, all 13 males among a total of 184 nurse teachers and students at one nursing school in Norway were interviewed twice with a 10-year interval between the interviews. In a personal interview in 1984 all the interviewees emphasized that their desire to become nurses was connected with a wish to act in a woman's role and expressed feminine values. The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…(e.g., Dodson andBorders 2006), U.K. (e.g., Simpson 2005;Whittock and Leonard 2003), and Scandinavia (e.g., Soerlie et al 1997). These equivocal findings are furthered by evidence from Rochlen et al (2009), who found that U.S. men in nursing and those in more traditional occupations experienced similar levels of gender role conflict.…”
Section: Experiences Within the Workplacementioning
confidence: 83%
See 1 more Smart Citation
“…(e.g., Dodson andBorders 2006), U.K. (e.g., Simpson 2005;Whittock and Leonard 2003), and Scandinavia (e.g., Soerlie et al 1997). These equivocal findings are furthered by evidence from Rochlen et al (2009), who found that U.S. men in nursing and those in more traditional occupations experienced similar levels of gender role conflict.…”
Section: Experiences Within the Workplacementioning
confidence: 83%
“…These reactions are often framed within larger societal expectations of masculinity. In the U.S. and Scandinavia, researchers have found that whereas some men have experienced mistrust, narrowed career opportunities, and challenges to their manhood (e.g., Allan 1993;Henson and Rogers 2001;Soerlie et al 1997), others report having been welcomed and offered enhanced career opportunities, including swift advancement, and choice trainings and placements (Hultin 2003;Sargent 2001;Williams 2013). Researchers in the U.S., Canada, Germany, and the U.K. have also found that interactions around gender role issues in female dominated work environments can increase men's distress due to Gender Role Conflict (Dodson and Borders 2006;Henson and Rogers 2001;Luhaorg and Zivian 1995;Simpson 2005) and gender role strain (Sobiraj et al 2015).…”
Section: Experiences Within the Workplacementioning
confidence: 97%
“…Participants who entered professions for these different reasons may have experienced the lack of male colleagues differently-either distressing and/or fulfilling. Men who entered nontraditional occupations reluctantly or as a second or more distant choice may experience the lack of male colleagues differently than those who entered for reasons of enjoyment, fulfillment, or other sources of intrinsic motivation (Simpson, 2005;Soerlie et al, 1997;Whittock & Leonard, 2003), which likely affects the emergence of gender role conflict or strain. This experience may be particularly true if these men find themselves unable to move out (or up) relatively quickly.…”
Section: Endorsement Of Masculinity Norms In the Nontraditional Work mentioning
confidence: 99%
“…Men in nontraditional occupations frequently experience comments and assumptions regarding their ambition, success, sexual orientation, and occupational status from friends, family members, colleagues, and themselves (Cross & Bagilhole, 2002;Dodson & Borders, 2006;Henson & Rogers, 2001;Simpson, 2005). Men have also experienced suspicion from service recipients (e.g., Soerlie, Talseth, & Norberg, 1997) as their presence in these jobs is perceived as violating male stereotypes and norms and posing threats to others.…”
Section: Research On Grc and Men In Nontraditional Occupationsmentioning
confidence: 99%
“…In addition, it was found that 24% of the students are interested in pharmacy and 16% preferred faculty of pharmacy because it is "a profession that offers respectable, comfortable, profitable and good future" ( Table 2). In other studies on students who prefer healthcare field in career selection, it was shown that factors such as indispensability of healthcare services, job guarantee, wide working area, importance given to health professions are effective in student's choice of profession [17,18]. These factors are thought to be also effective on students who prefer pharmacy faculties.…”
Section: Resultsmentioning
confidence: 99%